PENERAPAN MODEL PEMBELAJARAN SOMATIC, AUDITORY, VISUAL, INTELLECTUALY UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Astuti, Tri; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe aim of this research was to improve the result of student’s learning on the eleventh science grade of SMA Negeri 5 Singkawang in colloid material through Somatic, Auditory, Visualization, Intellectualy (SAVI) learning model. The form of this research was Classroom Action Reseacrh (CAR). Subject of this research 19 students on the eleventh grade of science of SMA Negeri 5 Singkawang. Observation sheet and test were used as instrument of research. Before using the instrument, it was tested it’s validity and realibility. The validity used Gregory test and the realibility used Alpha Chronbach formula. Based on the result of validity for each first cycle which was qualified in high category and the realibility in first cycle and second cycle were r11 =0.5215 which was in medium category and r11= 0.225 was in low category. The action in this research consisted of two cycles and serial cycles consist of four phases which are planning, acting, observing, and reflecting. The research result showed that there were improvement toward students learning result by implementing SAVI learning model. The percentage of students learning result in first cycle and second cycle were 57.89% and 78.94% respectively. Keyword: classroom action research, learning result, SAVI, colloid